The Yearly Nutation: The Euler’s Mechanical Moment Related to the Earth’s Centre - Ciobanu, Monica Zoe (European Journal of Applied Sciences, 2026)
The paper attempts, only approximately, to present when and where a wobble may appear and for how long it may persist along the Earth’s rotation axis, with external forces assumed to be the Moon’s tangential forces on its real orbit and the Sun’s on its apparent orbit. The paper also attempts to determine whether there are moments when no wobbles exist, and when the Earth’s rotation axis and the Earth’s kinetic moment are both aligned with the Oz terrestrial axis, pointing together to the real terrestrial north pole. The period investigated is the great nutation period of 18,6 years. An approximate calculation may suggest that this nutation with a periodicity of 18,6 years is due to wobbles caused by the Moon and the Sun.